2018
DOI: 10.1159/000493554
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Lesions of Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the leading causes of cancer death. Although the treatment modalities are improving, the prognosis of PDAC continues to be poor. Therefore, early detection of PDAC or its precursor lesions may be the best way to improve patient survival. PDACs have several different precursor lesions, including pancreatic intraepithelial neoplasias (PanINs), intraductal papillary mucinous neoplasms (IPMNs), intraductal tubulopapillary neoplasms (ITPNs), intraductal oncocytic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 87 publications
0
34
0
1
Order By: Relevance
“…With our findings above at hand, it would be highly relevant to test immune responses in patients with RAS -mutant cancers and clarify if these patients display an attenuated immune response to the mutant epitopes, which would add impetus to the notion of the evolution of RAS -mutant cancer due to tumor immune evasion. The translational relevance of our findings would be to identify patients with premalignant RAS -mutant lesions, such as patients with precursor pancreatic cancer lesions [ 41 ], and perform vaccinations with RAS -mutant-derived epitopes to enhance the RAS -mutant-specific immune response, in order to facilitate clearing of the pre-malignant lesion.…”
Section: Discussionmentioning
confidence: 99%
“…With our findings above at hand, it would be highly relevant to test immune responses in patients with RAS -mutant cancers and clarify if these patients display an attenuated immune response to the mutant epitopes, which would add impetus to the notion of the evolution of RAS -mutant cancer due to tumor immune evasion. The translational relevance of our findings would be to identify patients with premalignant RAS -mutant lesions, such as patients with precursor pancreatic cancer lesions [ 41 ], and perform vaccinations with RAS -mutant-derived epitopes to enhance the RAS -mutant-specific immune response, in order to facilitate clearing of the pre-malignant lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of normal pancreatic epithelium into malignant cells seems to cross in many cases through premalignant lesions, namely the pancreatic intraepithelial neoplasia (PanIN) and intraductal papillary mucinous neoplasm (IPMN) (32). In support of this hypothesis, genomic analysis of PanIN and IPMN showed that they share the same genetic alterations of PDAC, although with lower incidence (33).…”
Section: Pdac Evolution: From Pancreatic Gland To Metastasismentioning
confidence: 94%
“…Von pathohistologischer Seite werden dabei beschrieben bzw. neu definiert: pankreatische intraepitheliale Neoplasie (PanIns), intraduktal papillär muzinöse Neoplasie (IPMN), intraduktal tubulopapilläre Neoplasie (ITPN), intraduktal onkozytisch papilläre Neoplasie (IOPN), muzinös zystische Neoplasie (MCN) [22,23].…”
Section: Precursor Lesionsunclassified